Exploring Jesuit distinctiveness: interdisciplinary perspectives on ways of proceeding within the Society of Jesus - Maryks, Robert A. (Jesuit studies - modernity through the prism of Jesuit history, 2016)
The volume theme is the distinctiveness of Jesuits and their ministries. It explores the quidditas Jesuitica, or the specifically Jesuit way(s) of proceeding in which Jesuits and their colleagues operated from historical, geographical, social, and cultural perspectives. Thanks to generous support of the Institute for Advanced Jesuit Studies at Boston College, this volume is available in Open Access.--